Asuhan Keperawatan pada Ny. V dan Ny. S yang Mengalami Isolasi Sosial dengan Skizofrenia di Rumah Sakit Jiwa Dr. Soeharto Heerdjan Jakarta - Lissa, Agnesia; Prihatini, Fitria; Vestabilivy, Evi (STIKes Persada Husada Indonesia, 2024)
Schizophrenia is a mental disorder characterized by gross deviations and discrepancies in thinking, accompanied by abnormal emotional expression. Social isolation refers to disturbances in interpersonal relationships where individuals show symptoms of withdrawal and are not interested in interacting with other people. The aim of this research is to obtain an overview of nursing care for patients who experience social isolation problems with schizophrenia. This research design uses a qualitative approach with case study analysis. Participants in this study were 2 social isolation patients and nurses at RSJ Dr Soeharto Heerdjan. The medical diagnosis in both patients was schizophrenia (F.20). After conducting the assessment, the author found 6 nursing diagnoses that were the same in both patients, namely hallucinations, social isolation, low self-esteem, ineffective individual coping, ineffective therapy regimen, and risk of violent behavior, and one different diagnosis, namely self-care deficits found in Mrs. V. The objectives and outcome criteria for social isolation nursing care are achieved, namely that both patients can build a relationship of mutual trust, state the causes of withdrawal, state the advantages of social relations and the disadvantages of withdrawing, and can carry out social relations gradually.